Pertumbuhan dan Hasil Bawang Merah (Allium ascalonicum L.) Pada Beberapa Dosis Pupuk ZA dan Konsentrasi ZPT Atonik - Ikhwan Nurmahmudi; Benni Satria; Nurwanita Ekasari Putri (Jurusan Budidaya Pertanian Fakultas Pertanian Universitas Andalas, 2025)
Shallot (Allium ascalonicum L.) is one of the main horticultural commodities that is widely consumed as a condiment after chili. This research focuses on the interaction of the dose of ZA fertilizer with the concentration of ZPT Atonik on the growth and yield of shallot plants. This research was conducted in the experimental garden of Andalas University, Padang with an altitude of ± 383 meters above sea level, from March to May 2025. This experiment used a Factorial Randomized Group Design with two factors. The first factor is the dose of ZA fertilizer 0 kg/ha, 400 kg/ha, 800 kg/ha and the second factor is the concentration of ZPT Atonik 0 cc L-1, 0.50 cc L-1, 1 cc L-1. Data were analyzed by analysis of variance (ANOVA) and further analyzed by Duncan New Multiple Range test (DnMRT) at 5% significance level. The results showed an interaction between the dose ZA fertilizer with a concentration of ZPT Atonik on tuber diameter parameters. Doses of ZA fertilizer gave a significant effect on the number of leaves, number of tubers, fresh weight of tubers per clump, fresh weight of tubers per plot, dry weight of tubers per clump, and dry weight of tubers per plot.